Constitutional Voice for Good Governance in Bangladesh - Alam, Md. Ashraful; Hasina, Nusrat (Global Disclosure of Economics and Business, 2014)
Good governance is a real drive behind a country’s development. It protects the human rights, ensures the justice, maintains law an order and provides equal opportunities to the masses. It provides the fruits of progress and development to all and sundry. Participation, transparency and rule of law, are some essentials of good governance. It is a vital aspect at all levels of society and state. It makes the system of the state effective and efficient. Good governance is not well rooted in Bangladesh due to some challenges. Civil society is trying to focus the concept for smooth development and stability of a country. Because, people of the country enjoy equal rights where there is good governance. Minorities live freely and exercise their religion. Therefore, a welfare state can only exist if there is good governance.JEL Classification Code: K1